A prospective observational study on efficacy of ulipristal acetate in treatment of uterine fibroids - Singh, Eshna; Khanijo, Vandana; Unni, Jyothi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Uterine fibroids are common benign tumors where management has traditionally been surgical. Ulipristal acetate (UPA) is a new, effective, and well-tolerated option for the preoperative treatment of moderate and severe symptoms of uterine fibroids. Objectives were to study the utility of UPA in treatment of uterine fibroids. Methods: A prospective observational study was conducted in women aged 18-50 years presenting with menstrual abnormalities with fibroids to Jehangir Hospital, from 01 December 2017 to 30 September 2019. The 50 premenopausal women with at least one fibroid ≥3 cm in diameter and <8 cm, with heavy menstrual bleeding (HMB) or pain were included. 5 mg of UPA was given once daily for a period 3 months. Primary outcome was to determine symptomatic relief. Results: Uterine bleeding was controlled in 96% patients whereas 100% had pain relief. Reduction of fibroid volume and size was noted in 60% patients. Favourable outcomes were seen in more cases of intramural fibroids as compared to sub-serosal and submucosal fibroids. Conclusions: UPA proved to be an effective drug for symptomatic relief in patients with uterine fibroids. Although 60% patients showed reduction in fibroid size, the amount of reduction was not very significant in most of the patients.